2001
DOI: 10.1557/proc-665-c7.5
|View full text |Cite
|
Sign up to set email alerts
|

High Performance Organic Field-Effect Transistors and Integrated Inverters

Abstract: Integrated plastic circuits (IPCs) will become an integral component of future low cost electronics. For low cost processes IPCs have to be made of all-polymer Transistors. We present our recent results on fabrication of Organic Field-Effect Transistors (OFETs) and integrated inverters. Top-gate transistors were fabricated using polymer semiconductors and insulators. The source-drain structures were defined by standard lithography of Au on a flexible plastic film, and on top of these electrodes, poly(3-alkylth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 7 publications
2
7
0
2
Order By: Relevance
“…5 Field-effect mobilities up to 3.1 cm 2 /V s have been reported for crystalline small molecules 6 and values up to 0.1 cm 2 /V s for polymers have been demonstrated even on plastic substrates. 7 With respect to silicon substrates it has been reported that treating the SiO 2 gate oxide with a silylating agent such as hexamethyldisilazane ͑HMDS͒ promotes the self-organization properties of P3HT due to a hydrophobization of the SiO 2 surface. 3 To obtain highly ordered polymers in a preferred direction several different techniques have been applied, e.g., mechanical alignment in the form of rubbing or stretching, Langmuir-Blodgett deposition, liquidcrystalline self-organization, or the addition of alignment layers.…”
Section: Introductionmentioning
confidence: 99%
“…5 Field-effect mobilities up to 3.1 cm 2 /V s have been reported for crystalline small molecules 6 and values up to 0.1 cm 2 /V s for polymers have been demonstrated even on plastic substrates. 7 With respect to silicon substrates it has been reported that treating the SiO 2 gate oxide with a silylating agent such as hexamethyldisilazane ͑HMDS͒ promotes the self-organization properties of P3HT due to a hydrophobization of the SiO 2 surface. 3 To obtain highly ordered polymers in a preferred direction several different techniques have been applied, e.g., mechanical alignment in the form of rubbing or stretching, Langmuir-Blodgett deposition, liquidcrystalline self-organization, or the addition of alignment layers.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that the relevant physical parameters ͑e.g., charge carrier mobility͒ depend crucially on the structural order within the organic semiconductor. [1][2][3][4][5] For commercial applications, devices based on organic single crystals are not practical, rather, organic thin film devices are more likely to be used. Thus, it is necessary to find compounds which intrinsically exhibit the desired electronic properties and, at the same time, show high structural order in thin films.…”
mentioning
confidence: 99%
“…Die durch Simulation erhaltenen Ladungsträgerbeweglichkeiten betrugen maximal 0,05 cm 2 /Vs. Die Logikfähigkeit dieses Typs von Polymertransistoren wurde durch den Aufbau von Invertern belegt [20].…”
Section: Polymere Feldeffekttransistorenunclassified